Distribution of mucopolysaccharides in the adrenal gland of prenatal buffalo - SETHI, R S; ROY, K S; SINGH, OPINDER (The Indian Journal of Animal Sciences, 2013)
The study was conducted on the adrenal glands of 43 buffalo foetuses of 39 mm to 890 mm crown rump length (CRL) to investigate the distribution of mucopolysaccharides. The paraffin sections of adrenal glands were stained with PAS and AB-PAS methods to demonstrate the presence of neutral mucopolysaccharides (NMPS) and acid mucopolysaccharides (NMPS), respectively. The NMPS content was high in the inner aspect of the capsule, moderate in the wall of large blood vessels of the capsule, low in the definite and foetal cortex, and low to moderate in both the zones of the medulla. The AMPS content was low in the adrenal primordia and